Intraspecific morphological variation of crossbanded barb, Puntioplites bulu (Bleeker, 1851) from selected river in Peninsular Malaysia based on truss network analysis - A. Ghani, Intan Faraha; Arshad, Aziz; Harmin, Sharr Azni; Christianus, Annie; Ismail, Muhammad Fadhil Syukri (Universiti Putra Malaysia Press, 2018)
The study on intraspecific variation of wild crossbanded barb, Puntioplites bulu stock in Peninsular Malaysia was investigated based on truss network analysis constructed from the fish body. A total of 90 samples were collected from three different populations, namely Kelantan River, Perak River and Pahang River (n= 30/population). The 22 truss characters were standardised by an allometric formula and analysed by multi and uni-variate analysis. The results showed significant differences (p< 0.05) between mean of the three populations. The loadings of the first and second discriminant function accounted for 81.3% and 18.7% respectively in terms of group variability, and they explained 100% of the total among group variability. The results showed significant variation of P. bulu in morphology based on truss network caught from three different populations. The morphological differences were located mainly on the head region, body depth and median region. These findings indicate the presence of morphometric variations between three populations of P. bulu in Peninsular Malaysia based on their locations.